Literal and inferential English reading comprehension skills among multilingual Filipino elementary school children. [article]. - Intal, Anna Miren G.
The first part of the article presents an overview of the cognitive, psycholinguistic, and educational psychology research literature on basic reading and reading comprehension processes and skills which can serve as a resource for those who wish an introduction to the field. The second part of the article presents data on a study of literal and inferential English reading comprehension skills of 553 Grade one to Grade six multilingual Filipino elementary school children. The subjects read 12 passages that were constructed to approximate the difficulty levels of reading materials in the DECS prescribed English reading textbooks for the different grade levels in the Philippines. Each passage was followed by five questions, some literal and some inferential, which sought to determine the children's English reading comprehension skills. At the literal comprehension skills level, the questions dealt with remembering details read and remembering the sequence of events in the story. Ta the inferential comprehension skills level the questions dealt mainly with finding the main idea or theme of the passage, inferring character emotional reaction and characteristics of story character, drawing logical conclusions, determining word meaning from context, and inferring causal antecedents and causal consequences. The performance of the children in these skills across grade levels and passage difficulty levels is compared and insights are drawn on the development of these reading comprehension skills among the children.